The role of logistics in international crises and challenges - Khaled El Sakty (International Business Logistics Journal)
Considering the current economic and commercial challenges in some commercial areas in the world, and the accompanying with the climatic changes, the pandemics, trade tension, trade restrictions, and political conflicts, there has been a decline in the global trade flows (Free and Hecimovic, 2021). The global supply chain pressure has increased, and the length of chain became longer. As a result, there is a shortage of products and raw materials in some markets, high freight rates increased, and there is loss, damage, and delay in the goods movement (Qin et al., 2023). Strategically, most of companies aimed to use logistical solutions and strategies to avoid these effects, either through increasing inventory levels, relying on local suppliers, using applications of the 4th industry applications, or through mergers and alliances with other companies (Bygballe et al., 2023). However, these solutions and strategies led to an increase in the volume of invested capital, a rise in the rate of cybercrime, the congestion in seaports and airports, the increase in demurrage and detention, and the shortage of storage spaces. Among these challenges and strategies, logistics and supply chains become as one of the most important sciences at this critical stage in world history. Accordingly, logisticians regularly assess their operational performance and fix problems. They work together with suppliers and vendors to guarantee that all activities adhere to the highest standards of quality and safety. This requires from all logistics and supply chain managers to search and research for reliable, resilient, and innovative strategies, tools, and applications. At the end, the literature views supply chain as a pro-active strategy that employs a pre-established set of procedures to guard against disruptions (Suryawanshi and Dutta, 2022). To preserve balance and respond to unforeseen events, supply chain and logistics are advocated as proactive tactics.